Appendix 4.1: Foreword, Ferdinand E. Marcos on Human Rights - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Dean Froilan Bacungan was one of the editors of Ferdinand E. Marcos on Human Rights , which consists entirely of excerpts from the Marcos (ghostwritten) oeuvre, classified under chapters with titles such as “The Right to Dissent” and “Human Rights and Economic Development.” Though the editors claim that this was produced of their own volition (with Marcos’s imprimatur), there are signs that the book was produced with the help of Marcos propagandists, e.g., the book’s cover is a painting by Andres Cristobal Cruz, a mainstay of Marcos’s propaganda group.